When we do harm : a doctor confronts medical error - Ofri, Danielle (Beacon Press, 2020)
"Physician and author Danielle Ofri investigates how medical error could be killing 10% of patients and causing 33% of hospital deaths. These stories ask us to reconsider what happens when the medical system does us harm"--